PENGARUH PEMAHAMAN DAMPAK KORUPSI TERHADAP MINAT MASYARAKAT SEBAGAI CITIZEN CONTROL - Saadah; Syakieb Arsalan; Dini Verdania Latif (BAJ: Behavioral Accounting Journal, 2019)
Corruption is defined as "misuse of public office for personal gain". This definition leads to corruption being concentrated in the hands of the elite. Corruption interferes with governance practices, reducing public funds available to support economic growth programs, in turn, will reduce public trust in the government. To prevent corruption, the government develops e-government. The implementation of e-government aims to enable the government to provide information on the administration of government activities in a transparent and accountable manner and to make it easier for the public to access this information. With the ease of access, it is expected that the community can participate in overseeing the government activities as citizen control. The interest of the community as citizen control can also be influenced by people's understanding of the impact of corruption. If the public is aware of losses due to corruption, the community will be encouraged to monitor the government carefully. This study aims to determine the effect of understanding the impact of corruption on community interest as citizen control. This research is an explanatory research. Sample in this study are residents of the city of Bandung. The results of the study indicate that understanding the impact of corruption by the public has an effect on people's interest as citizen control.